Medicaid and the limits of state health reform - Sparer, Michael S. (Philadelphia : Temple University Press, 1996)
A critical look at state-dominated health care.
Acknowledgments; 1. The State Role in Health Care Reform: Why Do We Care?; 2. Congress Considers Health Reform; 3. Explaining Medicaid Variation; 4. The Medicaid Programs in New York and California; 5. Paying for the Institutionalized Aged: Lessons from Nursing Home Policy; 6. Alternatives to Institutionalization: Lessons from Home Care Policy; 7. Reducing the Cost of Hospital Care: Lessons from New York and California; 8. Moving Medicaid Clients into Managed Care; 9. States and the U.S. Health Care System; Notes; Index.
Includes bibliographical references (pages 203-228) and index.
Print version record.
JSTOR
Keywords: Health care reform -- United States -- States; Medicaid; Medical policy; Health planning; Medical care; Social control; Non-governmental organizations; Health services administration; Public welfare; Social sciences; Health care reform; Economics; Sociology; Health Policy; Medical Assistance; Government; Health Planning; Delivery of Health Care; Legislation as Topic; Public Policy; Social Control, Formal; Health Care Economics and Organizations; Health Care Quality, Access, and Evaluation; Organizations; Patient Care Management; Public Assistance; Social Sciences; Health Care Reform; State Government; Medicaid; Social Control Policies; Anthropology, Education, Sociology and Social Phenomena; Health Services Administration; Financing, Government; Policy; Financing, Organized; Economics; Sociology; Patient Care; Services de santé -- Réforme -- États-Unis -- États.; Medicaid; Politique sanitaire; Institutions politiques; Santé publique -- Planification; Prestation de soins; Contrôle social; Organisations non gouvernementales; Services de santé -- Administration; Aide sociale; Sciences sociales; Services de santé -- Réforme.; Aide de l'État.; Économie politique; Sociologie; Soins médicaux.; governments (administrative bodies); welfare services; social sciences; federal aid; economics